Congenital melanocytic nevus with surgical scar. - Cutrone, M. (European Journal of Pediatric Dermatology, 2011)
Case report. A child aged 14 months, eldest son, born by Cesarean section at 38 weeks, was first observed during a monitoring program of congenital melanocytic nevi. The physical examination showed a 4 cm in diameter congenital melanocytic nevus, equipped with darker and thicker hair. In the center of the nevus there was a white line, curve with the concavity facing forward and upward, of about 2 cm (Fig. 1). A supplement of history told us that the child at birth presented a bleeding linear wound in the same site. Dermoscopy examination (Fig. 2) showed a whitish scar without follicular openings. These findings led to the final diagnosis of linear, scalpel-induced scar on congenital melanocytic nevus. Monitoring of the nevus was programmed.